Comparison of Primary and Modular Nursing Methods on Nurse Work Engagement, Nurse Job Satisfaction, Patient Trust, and Patient Satisfaction in A General Hospital - Ni Putu Emy Darma Yanti; I Ketut Dian Lanang Triana; Rai Sekar Widhi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nursing care delivery models influence the continuity, quality, and outcomes of nursing care. Primary nursing and modular nursing present different approaches to responsibility distribution, care coordination, and nurse–patient interaction. However, evidence comparing their impact on nurse-related and patient-related outcomes remains limited in low- and middle-income countries. Aim to compare the effects of primary versus modular nursing methods on nurse work engagement, nurse job satisfaction, patient trust, and patient satisfaction in an inpatient setting. A cross-sectional comparative study was conducted among 60 nurses and 30 adult inpatients in a regional public hospital in Bali, Indonesia. Purposive sampling was used. Validated instruments were administered. Utrecht Work Engagement Scale (UWES) (Cronbach’s α = 0.80–0.90), Mueller & McCloskey Satisfaction Scale (MMSS) (reliability ranges from α = 0.78–0.89), Patient Trust Scale (PTS) (reliability α > 0.85), and Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ) (reliability α > 0.90). Data were analyzed using Chi-square tests with α=0.05. The primary nursing group demonstrated significantly higher levels of patient trust (p=0.038), patient satisfaction (p=0.041), nurse work engagement (p=0.027), and nurse job satisfaction (p=0.016) compared with the modular nursing group. Primary nursing consistently showed higher proportions in the “high” category across all measured outcomes. Primary nursing appears more effective than modular nursing in enhancing nurse work engagement and job satisfaction, while simultaneously improving patient trust and satisfaction. Wider adoption of primary nursing may support improvements in nursing care quality within hospital settings.